Ecological Indigenous Plants Used for the Treatment of Hypertension by the People of Ikhin Owan East Local Government Area, Edo State, Nigeria - Erhenhi. A.H. (Sokoto Journal of Medical Laboratory Science)
Survey of indigenous plants used in the treatment of hypertension by the people of Ikhin, Owan East Local Government Area, Edo State Nigeria was carried out. Hypertension is believed to be one of the leading causes of mortality in the world, representing 60% of all deaths. This survey was carried out to obtain knowledge and documentation of plants used in the treatment of hypertension. Ikhin is located at latitude 6 0 59’36” N of the equator and longitude 6 0 09’30” E of Greenwich Meridian. Twenty-seven (27) medicinal plants belonging to 21 families were used by the people of Ikhin in treatment of hypertension. The percentages of plant parts used indicated that leaves had the highest percentage of plant parts used (59.2%), next is the seeds (11.2%) while the least parts used were flowers and unripe fruits. The mode of preparations cum administration differs from one plant species to another. Ranging from the different parts of the plant parts used to the methods of preparation. While some plant parts are blended, squeezed, finely chopped or minced, some are soaked in cold water or ethanol, soaked in hot water, boiled, made into powdered forms or cut into smaller sizes.